Bitcoin and its Legality from Shariah Point of View - Yusuf Sani Abubakar; Ahmad Faosiy Ogunbado; Mpawenimana Abdallah Saidi (SEISENSE Journal of Management, 2018)
Bitcoin is a type of cryptocurrency and the most successful in blockchain management. It has become famous in recent years. The critical aspects of cryptocurrency are its legitimacy, source of money laundering, tax evasion, lack of regulation etc. The aim of this study is to explore the view of Muslim scholars on the legality of bitcoin with respect to Shariah. The study adopts doctrinal approach which utilizes descriptive approach of qualitative research methodology which relies on secondary data in form of text books, journals, newspapers, related websites etc. The study found that Muslim scholars are divided on the issue. A part of them completely rejected bitcoin and considered it against Shariah principles. On the other hand, some Muslim scholars believe bitcoin does not contradict Islamic principles and therefore may be used, however with certain conditions. The researchers tend to support the proponents’ view as most of the opponents’ grounds for the rejection are temporary in nature which may be covered through policy regulations.